Toward Indonesia as Global Maritime Fulcrum: Correcting Doctrine and Combating Non-Traditional Maritime Threats - Maula Hudaya; Agung Tri Putra (Universitas Airlangga, 2017)
Indonesia is the largest archipelagic country in the world and has enormous potentialin the maritime sector. Therefore, President Joko Widodo aimed to turn Indonesia into amaritime fulcrum of the world. However, this idea hampered by doctrinal errors rootedfrom the community level to policymakers, including the doctrine of state defense. Theseerrors rendered Indonesia unable to play an important role using its strategic location asthe largest archipelagic country. Furthermore, piracy culture in some coastal communitiesof Indonesia is also a problem that hinders international trade. Moreover, this conditionis further exacerbated by the threat of maritime terrorism that endangered Indonesianseafarers. This paper uses the theoretical foundation by Alfred Thayer Mahan on Sea Powerto analyze what kind of policies should be taken by the government to solve the maritimesecurity holes in order to actualize the idea of Indonesia as the maritime fulcrum of theworld. Mahen stated that to become a powerful country in the world, a country should havecontrol over the oceans. Through this theory, solving maritime security holes in Indonesiacan be conducted by accumulating the strength of the sea in quantity and quality.